Effects of Integrated Soil Fertility Management Practices on Soil Micronutrients and Maize (Zea Mays L.) Yields in Semi-Arid, Kenya - S. W. , Wamalwa; B.O , Danga; K Kenya , Kwena, (African Journal of Education,Science and Technology (AJEST), 2021)
Declining per capita crop yield in Sub-Saharan Africa is linked to widespread depletion of soil micronutrients due to non-conventional cropping systems that disregard optimal replenishment on smallholder farming systems. Use of Integrated Soil Fertility Management (ISFM) quickly and cheaply improves the levels of micronutrients needed for health crop production. However, assessments on micronutrients retention and effect on crop yields of soils in Arid and Semi-Arid Areas (ASALs) after ISFM adoption remains unknown at community level. The study was conducted in the Mwania watershed in Machakos County, Kenya between 2016 and 2018 to determine the effect of selected ISFM practices on soil micronutrients and maize yields at watershed level. About eighty-one farmers were randomly sampled; Nine ISFM farmers were superimposed on each of selected nine ISFM practices that were distributed uniformly across the watershed. Data was collected on soil micronutrients and maize yields. The aforementioned variables of interest were analysed using a one-way analysis of variance (ANOVA) in GENSTAT software version 15.1 computer program. Treatment means were separated using Duncan's Multiple Range test (DMRT) tests owing to the large number of treatments. The results showed maize yields increased after ISFM use compared to control regardless of cropping system. Combining 2 t/ha animal manure with 40 kg/ha of di-ammonium phosphate (DAP) fertilizer and tied ridging on either maize/pigeon pea or maize sole crop recorded highest 1.32 t compared to 1.38 t/ha of maize grain yields respectively compared to 0.88 t/ha (control) in short rains. During long rains, maize/pigeon pea intercrop alone was the highest at 1.577 t compared to 0.83 t/ha of maize grain yield from maize sole crop neither with fertilizer, animal manure nor tied ridging (control). It also significantly (≤ 0.05) increased soil iron (Fe) levels from 15.99 ppm (control) to 24.74 ppm. This was attributed to 0.14 % increases in soil pH (water) compared to control after speedy mineralization and dissipation of soil organic matter, which enhanced Fe solubilisation. Subsequently promoting rapid maize crop growth, avoiding adverse weather conditions ahead. Therefore, farmers in semi-arid areas could achieve desired maize yields with only 50% less than recommended fertilizer rates with ISFM practices that may reverse declining soil micronutrients and improve crop yields quickly and cheaply.